Perception of the Academic Lecturer’s Profile: From Research Orientation to Pedagogic Orientation, and Implications for the Digital Learning of Students - Yossel-Eisenbach, Yael; Gerkerova, Aleksandra; Davidovitch, Nitza (Journal of Education Culture and Society, 2024)
Aim. This study aims to examine the effect of lecturers’ teaching orientations, as perceived by students, on students’ digital learning patterns, differentiating between research-oriented and pedagogy-oriented teaching approaches.Methods. A survey method was employed to collect data from undergraduate students regarding their perceptions of their lecturers’ orientations and their own digital learning patterns. Descriptive statistical analysis, Pearson correlation, and mediation models were utilized to analyse the relationships between variables.Results. The findings indicate that when students perceived the lecturer as research-oriented, no significant indirect association mediated by the digital learning experience was found between the lecturer’s profile and both active and passive digital learning patterns. However, the association between the research-oriented lecturer and active digital learning was partially mediated by the student’s reading habits, while the association with passive digital learning was fully mediated by reading habits. For pedagogy-oriented lecturers, both active and passive digital learning patterns were partially mediated by the student’s learning experience, with no significant mediation by reading habits.Conclusion. The study suggests that research-oriented lecturers influence active digital learning through students’ reading habits, while pedagogy-oriented lecturers influence both active and passive digital learning through students’ digital learning experiences. Understanding these dynamics can help educational institutions support lecturers in their professional development and improve student learning outcomes in digital environments.